Conversion of waste polypropylene disposable cups into liquid fuels by thermal and catalytic pyrolysis using activated carbon - Ramesh Babu Aremanda; R.K. Singh (Center for Science and Technology, IAIN Surakarta, 2022)
Polypropylene plastics are used extensively in packaging and food services for short usage, poses enormous disposal problem and contributing to over 45 % of globally generated plastic waste. Accordingly, the present work is focused on converting waste polypropylene(WPP) disposable cups in to liquid fuels by employing thermal and catalytic pyrolysis processes. Characterization of WPP disposable cups were performed through proximate and ultimate analyses followed by TGA and found that 86% of its mass degrades in a temperature range of 430 – 603 oC. Effect of temperature in the range of 500 – 650 oC on liquid fuel production at a constant heating rate of 15 oC/min were noted in thermal pyrolysis, an optimum and stable liquid fraction of 76 % with a reaction time of 30 min was recorded at 500 oC. For studies on catalytic pyrolysis, activated carbon (AC) was applied from 470 to 530 oC at variable Feed to Catalyst (F/C) ratio of 1- 4, an optimum liquid yield of 74 % was obtained with a residence time of 35 min at 510 oC and F/C of 3:1. Thermo-physical properties of optimal liquid products were comparable with conventional fossil fuels. XRD and SEM analysis of AC catalyst were showed the presence of carbon at 24o and 42o of 2θ-angle with an apparel pore size of 2 µm.